Pengaruh Strategi Belajar terhadap Hasil Belajar Siswa SMK di Indonesia: Studi Meta Analisis - Ramadhani, Restu Kurnia; Iskandar, Ranu; Naryanto, Rizqi Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The purpose of this study was to evaluate the effect of learning strategies on the learning outcomes of vocational high school students in Indonesia. This study used a meta-analysis approach. Data were collected from Google Scholar and Semantic Scholar in February 2025. Keywords used Indonesian with a combination of